Chapter La bisbetica domata: proposta di lettura di Decameron IX 9 attraverso i proverbi e i novellieri toscani tra Tre e Quattrocento - Cellai, Valerio (Studi e saggi, 2020)
The essay focuses on the analysis and the use made by G. Boccaccio of a proverb inside Decameron IX.9. After a brief overview of the use of proverbs and auctoritates in the medieval rhetorical treatise and a summary of the studies over Boccaccio's utilization of proverbs, it will be tried to give an interpretation over the proverb in Decameron IX.9. Then it will be analyzed the comment over this proverb made by Raimondo d'Amaretto Mannelli and some rewriting of this novella by Franco Sacchetti, Giovanni Fiorentino and inside the Motti e Facezie del Piovano Arlotto.